Life insurance companies : analysis of policyholders' perception and financial benefits. - Lee, Choon Li. (2008)
This research project aims to find out which insurer is perceived by policyholders to be the “best insurance company”, the most important attribute(s) that an insurer should have and the most influential channel(s) of communication that affect(s) policyholder’s perception. In addition, we also try to identify the insurer that offers the highest financial benefits.